1991
DOI: 10.1177/095646249100200507
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Detection ofEntamoeba Histolyticain Homosexual Men

Abstract: In a study of bowel parasites in 128 Australian homosexual men attending a sexually transmitted diseases (STD) clinic, Entamoeba histolytica was detected in 37%, Giardia intestinalis in 3% and at least one protozoan in 81% of the group. There was no evidence of pathogenicity of E. histolytica, nor was there any association between the detection of E. histolytica and sexual practices, gastrointestinal symptoms, proctitis, human immunodeficiency virus antibody result or T-cell subset values. However it was noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…On the basis of the close social and economic relationship between Japan and Thailand and the fact that (i) sexual intercourse between homosexual men is closely associated with both HIV and amebic infections and (ii) comparison of genotypes between Thai and Japanese HIV strains indicates that a proportion of Japanese HIV strains were imported from Thailand (19,21,25,37,40), we hypothesized that the Japanese and Thai E. histolytica isolates might reveal a similar spectrum of genotypes that is indicative of similarities in the population structures of the E. histolytica strains between the two countries. However, our results appeared to argue against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the close social and economic relationship between Japan and Thailand and the fact that (i) sexual intercourse between homosexual men is closely associated with both HIV and amebic infections and (ii) comparison of genotypes between Thai and Japanese HIV strains indicates that a proportion of Japanese HIV strains were imported from Thailand (19,21,25,37,40), we hypothesized that the Japanese and Thai E. histolytica isolates might reveal a similar spectrum of genotypes that is indicative of similarities in the population structures of the E. histolytica strains between the two countries. However, our results appeared to argue against this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Entamoeba histolytica acquisition is via the fecal-oral route. In confined populations (e.g., men who have sex with men [MSM] visiting sex-on-premises venues), carriage rates are significantly higher than in the general population once the organism has been established secondary to various oral-anal sexual practices (173,254,274). As the risks for HIV acquisition and parasite acquisition in these environments overlap, apparent associations between E. histolytica and immunosuppression exist.…”
Section: Entamoeba Histolyticamentioning
confidence: 99%
“…In another study, Law et al (8) reported a 37% prevalence of Entamoeba in men who have sex with men. However, these studies did not differentiate E. histolytica from E. dispar or E. moshkovskii.…”
mentioning
confidence: 99%
“…To date, several microscopy-based epidemiological surveys to study the prevalence of E. histolytica and E. dispar have been performed in different parts of Australia, but they were carried out without using molecular methods to accurately identify the presence of individual species. Hence, none of these studies have determined the true presence of E. histolytica, E. dispar, or E. moshkovskii (8,14).…”
mentioning
confidence: 99%